The trans-well coculture of human synovial mesenchymal stem cells with chondrocytes leads to self-organization, chondrogenic differentiation, and secretion of TGFβ - Kubosch, Eva Johanna (Stem Cell Res Ther, 2016)
BACKGROUND: Synovial mesenchymal stem cells (SMSC) possess a high chondrogenic differentiation potential, which possibly supports natural and surgically induced healing of cartilage lesions. We hypothesized enhanced chondrogenesis of SMSC caused by the vicinity of chondrocytes (CHDR). METHODS: Human SMSC and CHDR interactions were investigated in an in-vitro trans-well monolayer coculture over a time period of up to 21 days. Protein expression was analyzed using histology, immunostaining, or enzyme-linked immunosorbent assay. Additionally, mRNA expression was assessed by quantitative PCR. RESULTS: After 7 days, phase-contrast microscopy revealed cell aggregation of SMSC in coculture with CHDR. Afterwards, cells formed spheres and lost adherence. However, this phenomenon was not observed when culturing SMSC alone. Fluorescence labeling showed concurrent collagen type II expression. Addition of transforming growth factor beta (TGFβ) to the cocultures induced SMSC aggregation in less time and with higher intensity. Additionally, alcian blue staining demonstrated enhanced glycosaminoglycan expression around SMSC aggregates after 1 and 2 weeks. Although TGFβ mRNA was expressed in all SMSC, the protein was measured with constantly increasing levels over 21 days only in supernatants of the cocultures. Considering the enhanced mRNA levels following supplementation with TGFβ, a positive feedback mechanism can be supposed. In line with the development of a chondrogenic phenotype, aggrecan mRNA expression increased after 7 and 14 days in the cocultures with and without TGFβ. Coculture conditions also amplified collagen type II mRNA expression after 2 weeks without and already after 1 week with TGFβ. There was no difference in collagen type I and type X expression between SMSC alone and the coculture with CHDR. Expression of both collagens increased following addition of TGFβ. mRNA data correlated with the intensity of immunofluorescence staining. CONCLUSIONS: Paracrine effects of CHDR induce a chondrogenic phenotype in SMSC possibly mimicking joint homeostasis. Coculture approaches may lead to a better understanding of cellular interactions with potential implications for cartilage repair procedures.